The Association Vitamin D and Left Ventricular Hypertrophy in Metabolic Syndrome Patients - Charles Limantoro; Andreas Arie Setiawan; Nur Alaydrus; Theofilus Ardy Pradhana; Friska Anggraini Helena Silitonga (RSUP Dr. Kariadi, 2025)
Background: Vitamin D deficiency is common, especially in people with metabolic syndrome. This condition increases the risk of cardiovascular problems, including left ventricular hypertrophy (LVH). While the connection between metabolic syndrome and LVH is well-documented, it is still unclear whether vitamin D deficiency alone contributes to the development of LVH in these patients. Aim: To study the association between vitamin D levels and LVH in patients with metabolic syndrome. Methods: A cross-sectional study was conducted with 38 patients diagnosed with metabolic syndrome in Kariadi Hospital, Semarang. Serum vitamin D levels were measured using the ELISA method, and LVH was diagnosed via echocardiography. Patients were categorized into normal and LVH groups. Vitamin D levels were classified as sufficient, insufficient, or deficient. The relationship between vitamin D levels, metabolic syndrome components, and LVH was analyzed. Results: Our findings revealed no significant difference in vitamin D levels between patients with LVH and those without it (mean 19.98 ± 5.59 ng/mL for the LVH group vs. 20.91 ± 6.56 ng/mL for the normal group, p=0.65). However, patients with LVH had a significantly higher number of metabolic syndrome components compared to those without LVH (p=0.044). Conclusion: While no direct association was found between vitamin D levels and LVH, the cumulative burden of metabolic syndrome components plays a significant role in the development of LVH. Future research should explore larger populations to investigate the therapeutic potential of vitamin D in cardiovascular outcomes.